Optimization Methodology for Supercritical Co2 Extraction of Resveratlor From Mulberry Leaves - Berdieva Zulfiya Mukhiddinovna; Mukhamadiev Bakhodir Temurovich (Peerian Journals Publishing, 2022)
Mulberry berries (white, red and black) contain a large number of substances useful for the human body: simple sugars (glucose and fructose), organic acids, essential oils, vitamins (water- and diro-soluble). Carotenes. A whole range of micro and macro elements. The content in the fruits of the strongest near-bottom antioxidants - carotenes, vitamins C.E. resveratrol and selenium - relieves the aging body of many diseases and has a rejuvenating property
Keywords: Mulberry berries; SC-CO2